Extensive Variation in Drought-Induced Gene Expression Changes Between Loblolly Pine Genotypes - Li, Jingjia; West, Jason B.; Hart, Alexander; Wegrzyn, Jill L.; Smith, Matthew A.; Domec, Jean-Christophe; Loopstra, Carol A.; Casola, Claudio (Frontiers in Genetics, 2021)
Drought response is coordinated through expression changes in a large suite of genes. Interspecific variation in this response is common and associated with drought tolerant and sensitive genotypes. The extent to which different genetic networks orchestrate the adjustments to water deficit in tolerant and sensitive genotypes has not been fully elucidated, particularly in non-model or woody plants. Differential expression analysis via RNA-seq was evaluated in root tissue exposed to simulated drought conditions in two loblolly pine (Pinus taeda L.) clones with contrasting tolerance to drought. Loblolly pine is the prevalent conifer in southeastern U.S. and a major commercial forestry species worldwide. Significant changes in gene expression levels were found in more than 4,000 transcripts (drought-related transcripts, or DRTs). Genotype by Environment (GxE) interactions were prevalent, suggesting that different cohorts of genes are influenced by drought conditions in the tolerant vs. sensitive genotypes. Functional annotation categories and metabolic pathways associated with DRTs showed higher levels of overlap between clones, with the notable exception of GO categories in upregulated DRTs. Conversely, both differentially expressed transcription factors (TFs) and TF families were largely different between clones. Our results indicate that the response of a drought tolerant loblolly pine genotype versus a sensitive genotype to water limitation is remarkably different on a gene-by-gene level, although it involves similar genetic networks. Upregulated transcripts under drought conditions represent the most diverging component between genotypes, which might depend on the activation and repression of substantially different groups of transcription factors.